Localization of sensory mechanisms utilized by coral planulae to detect settlement cues. Issue 3 (24th June 2013) - Tran, Cawa; Hadfield, Michael G.
Abstract Coral planulae are induced to settle and metamorphose by contact with either crustose coralline algae or marine bacterial biofilms. Larvae of two coral species, Pocillopora damicornis and Montipora capitata, which respond to different metamorphic cues, were utilized to investigate the sensory mechanisms used to detect metamorphic cues. Because the aboral pole of the coral planula is the point of attachment to the substratum, we predicted that it is also the point of detection for cues. To determine where sensory cells for cues are localized along the body, individual larvae were transversely cut into oral and aboral portions at various levels along the oral–aboral axis, and exposed to settlement‐inducing substrata. Aboral ends of M. capitata metamorphosed, while oral ends continued to swim. However, in larvae of P. damicornis, ¾ oral ends (i.e., lacking the aboral pole) were also able to metamorphose, indicating that the cells that detect cues may be distributed along the sides of the body. These cells do not correspond to FMRFamide‐immunoreactive cells that are present throughout the body. Cesium ions induced both aboral and oral ends of larvae of both species to settle, suggesting that oral ends have not lost their capacity to metamorphose, despite lacking sensory cells to detect natural cues. To determine whether sensory cells in larvae of P. damicornis are restricted to one side of the body, swimming behavior over substrata was observed in larvae labeled with diI, a red fluorescent lipophilic membrane stain. The larvae were found to rotate around the oral–aboral axis, with their surface against the substratum, not favoring a particular side for detecting cues. While clarifying the regions of the larval body important for settlement and metamorphosis in coral planulae, we conclude that significant differences between coral species may be due to differences in the distribution of sensory structures in relation to different planular sizes.